Anonymous
Anonymous asked in Science & MathematicsMathematics · 9 years ago

Determine the second order Taylor formula for the given function about (xo,yo)?

f(x,y) = cosye^(x-1)^(2), where xo = 1, yo = 0

1 Answer

Relevance
  • kb
    Lv 7
    9 years ago
    Favorite Answer

    Assuming that we have f(x,y) = e^((x-1)^2) * cos y:

    f(1, 0) = 1

    f_x = 2(x-1) e^((x-1)^2) * cos y ==> f_x(1, 0) = 0

    f_y = -e^((x-1)^2) * sin y ==> f_y(1, 0) = 0.

    f_xx = [2 * e^((x-1)^2) + (2(x-1))^2 e^((x-1)^2)] cos y ==> f_xx (1, 0) = 2

    f_xy = -2(x-1) e^((x-1)^2) * sin y ==> f_xy(1, 0) = 0

    f_yy = -e^((x-1)^2) * cos y ==> f_yy (1, 0) = -1.

    Hence,

    f(x, y) = 1 + 0(x - 1) + 0(y - 0) + (1/2!) [2(x - 1)^2 + 2 * 0(x - 1)(y - 0) + (-1)(y - 0)^2] + ...

    .........= 1 + (x - 1)^2 - (1/2)y^2 + ...

    I hope this helps!

Still have questions? Get your answers by asking now.